The Journey Within: Sri Aurobindo’s vision in Savitri - Krishnamohan, R (International Journal of Psychosocial Rehabilitation, 2020)
Sri Aurobindo explores the interplay between the individual soul and the Universal Soul in his epic poem Savitri: A Legend and a Symbol. The moment the spiritual seeker rejects material pleasures and frees himself from egoism, and surrenders to the Divine, He takes the burden of fighting the battle for the individual against the evil forces- external and internal-that bound him to the earthly plane, removes the cosmic mask of illusion, and reveals Himself. Aswapathi who is on a spiritual journey symbolizes the individual soul.